XML JATS in OJS: contributions towards integrating markup process and galley generation in diverse contexts - Soler, Santiago (2025)
This document presents the SUMARC project (UNLP System for Scientific Journals Markup), developed by the PREBI-SEDICI team at the National University of La Plata (UNLP), Argentina. The primary goal is to achieve editorial sovereignty and technological independence by creating a JATS XML markup workflow fully integrated into Open Journal Systems (OJS), overcoming the dependence on external tools such as Marcalyc or SciELO. The proposed system addresses three critical stages of the editorial process: - Conversion: Use of the docxConverter tool to transform DOCX files into JATS XML. - Editing and Enrichment: Integration of a Citation Parser for the automated conversion of references (initially based on APA 7) and the use of the OpenAlex API to validate metadata and correct errors via DOI. Additionally, the Texture editor was updated and migrated to ensure compatibility with OJS 3.4. - Presentation: Improvement of the JATS Parser plugin to enable the generation of PDF/A files from customizable templates, allowing each journal to define its own visual identity. Currently, SUMARC is already being used by 10 scientific journals at UNLP, and the code has been shared with the global community through GitHub repositories. Future work focuses on expanding supported citation standards and simplifying template design using HTML/CSS and Smarty